2022
DOI: 10.1108/ijqss-08-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Brazilian health-care professionals during the pandemic

Abstract: Purpose Health-care professionals are caring for patients in unprecedented circumstances during the COVID-19 pandemic, dealing with scarce resources, higher demand and uncertain outcomes. In this context, the purpose of this study is to explore the views of health-care professionals regarding their work conditions and perceived impacts of the pandemic on their health, as well as the role of resilience and improvisation in face of the new challenges. Design/methodology/approach This exploratory and qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Individuals reflected upon their own strength; “I never thought I could be so strong” ( Sun et al, 2020 ). The importance of being present in the moment was highlighted by HCWs who were; “learning to appreciate even smaller thigs such as “waking up early and watching the sunrise ( Araujo, Siqueira, & Amaral, 2022 ) or that “being alive should not be taken for granted any more. Now, I will never miss any chance to say nice things about my neighbors to their face, in case I don't meet them again during my life.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals reflected upon their own strength; “I never thought I could be so strong” ( Sun et al, 2020 ). The importance of being present in the moment was highlighted by HCWs who were; “learning to appreciate even smaller thigs such as “waking up early and watching the sunrise ( Araujo, Siqueira, & Amaral, 2022 ) or that “being alive should not be taken for granted any more. Now, I will never miss any chance to say nice things about my neighbors to their face, in case I don't meet them again during my life.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that this pandemic (COVID-19) has left us with feelings of uneasiness, fear, and instability, among other things, and the pressure in the workplace is greater than ever [ 55 , 56 ]. The effects of the COVID-19 pandemic and the workload on health professionals were examined [ 57 ]. Workload pressure, task dependency, professional isolation, and familial involvement in work, job uncertainty, fear of infection, financial loss, stigma, and social exclusion are all major stressors for working people [ 58 , 59 , 60 ], and these stressors may strengthen psychological distress.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%